The Impact of Active Learning Strategies on Developing EFL College Students’ Self-efficacy and Academic Achievement - Khansa Hassan Hussein Al-Bahadli ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The goal of this study was to see how active learning practices affected self-efficacy and academic accomplishment. Total of (59) male and female students from Imam AlKadhum University College’s English department were chosen from the third year, (29) male and female students for the experimental group and (30) male and female students for the control group. To achieve the aims of the study, a scale of self-efficacy and an achievement test in the educational guidance material were used. Appropriate approaches were used to verify the scale's validity and reliability. The study's findings found that there were statistically significant differences in self-efficacy and academic accomplishment between the twogroups of students, favoring the experimental group. The study's findingssuggest that active learning methodologiesshould be used in a variety of subjects and at various academic levels.DOI 10.54633/2333-021-042-036